Pengaruh Dukungan Sosial Terhadap Minat Belajar Siswa di Desa Neglasari - Fazrina Andriani Sakinah Lubis; Yannefri Bakhtiar; Amiruddin Saleh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Education is an effort to humans develop knowledge and potential, superior human resources (HR) is affected of external and internal factor, external factor is environment, culture and teacher whereas internal factor is family. The family has a function for as good place in carrying private and social education. Indonesia’s education index still in the low position, meaning that it need a support not only from the government but also the role of the family. This report aim to analyze the effect of social support on student in Neglasari village. The methods used in this research are interview, observation and literature study. Communities in Neglasari still lack of understanding related to education, on the one hand the community hopes that children can continue their study to the higher level but have are limited by family economic problem. Child friendship environmental factor can affect education, negative environmental factors have a risk not continue grade and graduating from school. Lack of parent motivation as a child ages have an affect decrease children motivation.